Sex, Intimacy, and Desire among Men of Chinese Heritage and Women of Non-Asian Heritage in Toronto, 1910–1950 - Chenier, Elise (Urban History Review / Revue d'histoire urbaine, 2014)
Because few women of Chinese heritage came to Canada, Chinese migrant communities before 1950 are described as “bachelor societies.” Sojourners’ own ambition to return home with more wealth, the imposition of ever-increasing head taxes on migrants from China, the 1923 Chinese Exclusion Act, and deeply entrenched racism toward people of Chinese heritage meant that the vast majority were doomed to live their lives without the emotional, material, or domestic support or companionship provided by wives and children. They were de facto bachelors, if not bachelors in fact. New research, however, shows that since the 1910s young men of Chinese heritage carved out spaces for themselves in Toronto’s urban sexual culture, and young white women a space for themselves in Toronto’s Chinatown. During the first half of the twentieth century, many men of Chinese heritage enjoyed sex, companionship, love, and family life. Perhaps as many as a third were married to or lived common-law with women of white heritage, and many more frequently engaged in sexual and intimate relationships with sex workers they sometimes sought as long-term companions. The evidence presented here challenges the current perception that “Chinese bachelors” lived sexless, loveless lives. These relationships were not without controversy, of course, but many people within the community accepted them, and women of white heritage, including sex workers, were integrated into the community in diverse ways.